Ribat Sheikh Al-Shuyukh in Baghdad 450-656 H. / 1058-1258 AD. - Obeidat , Adnan (Dirasat: Human and Social Sciences, 2022)
Robat, along with educational institutions, helped to spread scientific and religious life in Baghdad. Ribat Sheikh Al-shuyukh was one of the Robat which served scholars and Sufis and students of science since its establishment in 450H./1058AD. Until the Mongols entered Baghdad in the year 656H./1258AD. Sheikh Al- shuyukh received official sponsorship from the Caliphate Foundation, and from the Seljuk state represented by its minister Nizam al-Mulk, where their policies are met in supporting Sufi, with the aim of spreading the Sunni sect and attracting Sunni scholars, this gave Ribat Sheikh Al- shuyukh semi-official character, unlike the rest of the Robat. Therefore, this study seeks to shed light on this Ribat, whose sheikhdom was hereditary. Some of its shuyukh had official positions in the state, and the Sheikh of Ribat Sheikh Al- shuyukh were assigned by the Caliphate in official duties.